전라남도 특수학급 언어치료지원 운영 실태와 특수교사 인식 - 황우아(Woo A Hwang); 이은경(Eun Kyoung Lee) (언어치료연구, 2016)
목적: 본 연구는 치료지원 서비스 도입 이후 특수교사가 현장에서 느끼는 언어치료지원 서비스의 실태와 이들의 인식을 살펴봄으로써 성공적인 치료지원을 제공하기 위한 초석을 마련하는데 목적이 있다. 방법: 연구대상은 전라남도 15개 지역 초·중·고 특수학급에 재직 중인 특수교사 66명으로 이들에게 언어치료지원 서비스 실태, 치료지원에 대한 교사의 인식, 언어치료지원 서비스에 대한 향후 개선사항에 대한 의견으로 나누어 조사한 후 결과를 분석하였다. 결과: 첫째, 언어치료지원 서비스 실태조사 결과, 대상아동 장애유형은 정신지체, 의사소통장애 순으로 많았으며, 대부분의 대상아동의 수용언어 및 표현언어가 전반적으로 늦음이 가장 많았다. 한 학급에 언어치료지원 서비스를 받는 아이들은 한 학급당 1명, 주1회 서비스가 가장 많이 나타났다. 둘째, 언어치료지원 서비스를 이용하고 있는 교사의 인식을 조사한 결과, 치료지원 회기, 치료지원 지침, 치료지원 기간, 교외 방과 후와의 차이를 알고 있는지를 묻는 질문에 ‘아니요’라는 답변이 가장 많았다. 또한 특수교사들은 하루에 치료대상 아동 수는 5명 이하가 적당하고 생각하였으며, 주당 치료회수는 2회, 한 아동 당 서비스 기간은 현재의 10개월이 아닌 12개월이 적당하다고 답하였다. 셋째, 치료지원에 대한 향후 개선 사항에 대한 조사 결과, 치료사의 수 확충과 특수교육지원센터에 치료사 2인 이상 배치를 희망하는 것으로 나타났다. 또한 아동 한 명 당 지원횟수를 늘려 치료하는 것을 요구하였으며, 대상아동은 생활연령과 언어연령의 차이 큰 순서로 선정하는 것이 적절하다에 많은 응답을 보였다. 결론: 효율적인 치료지원을 위해 교육 현장에 있는 특수교사들의 정확한 이해가 필요한 시점에서 본 연구는 중요한 의미를 갖는다. 언어치료지원 서비스가 치료시간 내의 치료뿐만 아니라 특수교사와 치료사의 협력을 통해 치료지원이 성공적 발전방향을 모색하는데 도움이 될 것으로 기대한다. Purpose: Therapy support services cover a diverse array of fields, and as rehabilitation treatments improved over time, the demands of students with disabilities and their parents diversified, requiring therapy support services of a higher quality. Methods: Sixty-six local special education instructors from 15 special education classes providing speech therapy support in Jeollanam-do were surveyed. Speech therapy support was examined according to the demographics of the students receiving the speech therapy support, the extent to which the speech therapy support was carried out, the availability of the speech therapy support, and the cooperation of the special education instructor in speech therapy support. Results: First, with regard to speech therapy support, mental retardation and communication disorders were the most prevalent types of disability in students receiving support, in decreasing order, while most students with disabilities were generally late in developing receptive and expressive language. Second, with regard to the perception of instructors using speech therapy support services, “no” was the most common answer as to whether or not there appeared to be differences in the number of therapy support sessions, guidelines for therapy support, duration of the therapy support, and extracurricular activities among the students. Third, with regard to potential improvements for the future, the instructors hoped for an increase in the number of therapists and placement of more than two special education support center therapists per program. Conclusions: The current study is significant in that, at the time of the study, an accurate understanding of the opinions of special education instructors in educational environments was needed for the sake of developing successful therapy support services. With regard to speech therapy support, both the therapy provided during the treatment sessions and the cooperation between the special education instructors and the therapists may help in finding a successful direction for the development of therapy support. KCI Citation Count: 5